2009
DOI: 10.1093/jxb/erp226
|View full text |Cite
|
Sign up to set email alerts
|

Developmental changes and organelle biogenesis in the reproductive organs of thermogenic skunk cabbage (Symplocarpus renifolius)

Abstract: Sex-dependent thermogenesis during reproductive organ development in the inflorescence is a characteristic feature of some of the protogynous arum species. One such plant, skunk cabbage (Symplocarpus renifolius), can produce massive heat during the female stage but not during the subsequent male stage in which the stamen completes development, the anthers dehisce, and pollen is released. Unlike other thermogenic species, skunk cabbage belongs to the bisexual flower group. Although recent studies have identifie… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

4
38
0

Year Published

2009
2009
2024
2024

Publication Types

Select...
3
1
1

Relationship

1
4

Authors

Journals

citations
Cited by 22 publications
(42 citation statements)
references
References 59 publications
4
38
0
Order By: Relevance
“…Under both conditions, cyanide-resistant oxygen uptake was almost completely inhibited by the AOX inhibitor n-propyl gallate. When compared with the previously determined values for S. renifolius (Ito-Inaba et al 2009), all respiratory activities of state 2, 3, and alternative respiration from L. camtschatcensis were less than half those of S. renifolius. Taken together, these results suggest that lower mitochondrial density and respiratory activity may be correlated with the lack of thermogenesis in L. camtschatcensis.…”
Section: Resultsmentioning
confidence: 57%
See 4 more Smart Citations
“…Under both conditions, cyanide-resistant oxygen uptake was almost completely inhibited by the AOX inhibitor n-propyl gallate. When compared with the previously determined values for S. renifolius (Ito-Inaba et al 2009), all respiratory activities of state 2, 3, and alternative respiration from L. camtschatcensis were less than half those of S. renifolius. Taken together, these results suggest that lower mitochondrial density and respiratory activity may be correlated with the lack of thermogenesis in L. camtschatcensis.…”
Section: Resultsmentioning
confidence: 57%
“…In a previously published study (Ito-Inaba et al 2009), we found that mitochondrial density and respiratory activity in spadices of S. renifolius were much higher than in nonthermogenic plants, such as potato (Solanum tuberosoum L. cv. Danshaku) and cauliflower (Brassica oleracea L. botrytis).…”
Section: Resultsmentioning
confidence: 78%
See 3 more Smart Citations